KEANEKARAGAMAN JENIS JAMUR MAKROSKOPIS DI KAWASAN HUTAN SEKUNDER AREAL IUPHHK-HTI PT. BHATARA ALAM LESTARI KABUPATEN MEMPAWAH - Priskila, .; Ekamawanti, Hanna Artuti; Herawatiningsih, Ratna (Universitas Tanjungpura, 2018)
Macroscopic fungi have an important role for sustainable forest ecosystems. This study aims to describe the diversity of macroscopic fungi species in secondary forest areas in the area of IUPHHK-HTI PT. Bhatara Alam Lestari Bukit Batu village of Mempawah districk. This research used survey method with purposive sampling technique and macroscopic fungi inventory using a 5m Ã— 5m double plot of 14 plots with total area of 0.035 ha observation plot. In the study sites, 33 macroscopic fungi were found from 15 families, namely Agaricaceae, Boletaceae, Ganodermataceae, Hygrophoraceae, Inocybaceae, Marasmiaceae, Meruliaceae, Mycenaceae, Physalacriaceae, Polyporaceae, Psathyrellaceae, Sarcoscyphaceae, Stereaceae, Strophariaceae and Xylariaceae. The highest number of Polyporaceae family species were Lentinus squarosulus, Polyporus arcularia, Microporus affinis, Microporus sp., Tremetes versicolor, Tremetes sp. (1) and Tremetes sp. (2). Macroscopic fungi were found to have benefits for humans as foodstuffs such as B. suptomentosus, R. caperata, L. squarosulus, P. arcularia and C. Tricholoma. Species which were benefited as medicines Ganoderma sp., G. lucidum, G. applantum, G. tesugae, G. boninense and X. Polymorpha. Where as species which were benefited as souvenirs were Microporus sp., M. afinis, Stereum sp. and Stereum osrea. Macroscopic fungi that have ecological benefits as saprophytes were Leucocoprinus sp., Lepiota sp., Ganoderma sp., G. lucidum, G. applantum, G. tesugae, G. boninense, Hygrocibe sp., H. miniata, R. caperata, M. scorodonius, M. haematocepala, C. septentrionalis, Mycena sp., M. panaeolus, M. delicatella, C. asprata, L. squarosulus, P. arcularia, Microporus sp., M. afinis, T. versicolor, Tremetes sp. (1), Tremetes sp. (2), P. condolleana, C. tricholoma, Stereum sp., Stereum osrea, G. leiteopiridis, G. braendlei, X. polymorpha. Macroscopic fungi which have ecological benefits as ectomycorrhiza namely Tylopilus sp. and B. suptomentosus.Keywords: Edible mushroom, Macroscopic Fungi, Polyporaceae, saprophyte, Secondary Forest.